Brucella abortus is Prevalent in Both Humans and Animals in Bangladesh. (9th January 2017) - Rahman, A. K. M. A.; Saegerman, C.; Berkvens, D.; Melzer, F.; Neubauer, H.; Fretin, D.; Abatih, E.; Dhand, N.; Ward, M. P.
Summary: To determine the role of different Brucella ( B .) spp. in Bangladesh, 62 animal samples and 500 human sera were tested. Animal samples from cattle, goats and sheep (including milk, bull semen, vaginal swabs and placentas) were cultured for Brucella spp. Three test‐positive human sera and all animal samples were screened by Brucella genus‐specific real‐time PCR (RT‐PCR), and positive samples were then tested by IS711 RT‐PCR to detect B. abortus and B. melitensis DNA . Only B. abortus DNA was amplified from 13 human and six animal samples. This is the first report describing B. abortus as the aetiological agent of brucellosis in occupationally exposed humans in Bangladesh. Of note is failure to detect B. melitensis DNA, the species most often associated with human brucellosis worldwide. Further studies are required to explore the occurrence of Brucella melitensis in Bangladesh.